2023
DOI: 10.1002/slct.202301247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights on the Modulated Acetylcholinesterase Inhibition Activity of Tacrine Adsorbed on Biocompatible Graphene Oxide

Abstract: Graphene oxide (GO) based nano‐formulation has gained much attention because of its carbonaceous composition with biologically benign properties. In this study, the interactions of GO with tacrine (TAC), an FDA approved Alzheimer's disease (AD) drug, are explored using various analytical tools and theoretical modeling techniques. Furthermore, the modulatory effect of these nano‐conjugates toward the in‐vitro catalytic activity of the neurodegenerative enzyme acetylcholinesterase (AChE) is also quantified. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…In a recent communication, it has been reported that certain antidiabetic drugs of sulfonylurea class are extremely potent in inhibiting acetylcholinesterase (AChE) activity, suggesting their possible application in the treatment of Alzheimer’s disease (AD) . Additionally, latest research findings from one of the present research groups indicate that tacrine (TAC), an FDA-approved AD medication, might also be effective in reversing the DNA oxidative stress caused by reactive oxygen species (ROS). , Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a recent communication, it has been reported that certain antidiabetic drugs of sulfonylurea class are extremely potent in inhibiting acetylcholinesterase (AChE) activity, suggesting their possible application in the treatment of Alzheimer’s disease (AD) . Additionally, latest research findings from one of the present research groups indicate that tacrine (TAC), an FDA-approved AD medication, might also be effective in reversing the DNA oxidative stress caused by reactive oxygen species (ROS). , Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction …”
Section: Introductionmentioning
confidence: 81%
“…8,9 Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction. 10 The incorporation of nanotechnology into medical research marks a significant advancement, especially in the development of innovative therapeutic strategies. 11−15 This is particularly visible in the judicious integration of nanomaterials with biological mechanisms, which holds the promise of transforming the way diseases are treated at both the molecular and cellular scales.…”
Section: Introductionmentioning
confidence: 99%